The nexus between agricultural exports and food security in Zimbabwe - Kondo, Talent; Tambudzai, Zachary (Annals of Management and Organization Research, 2025)
Purpose: This study aimed to evaluate the relationship between agricultural exports and food security in Zimbabwe from 1990 to 2023. Research Methodology: A time-series analysis was conducted using the Ordinary Least Squares (OLS) method and autoregressive distributed lag (ARDL) bounds testing approach to examine both short-run and long-run dynamics. Diagnostic tests, such as ADF, multicollinearity, heteroskedasticity, and serial correlation, were performed to ensure robustness.   Results: The findings revealed that agricultural exports had a positive and statistically significant effect on food security. A 1% increase in agricultural exports leads to a 0.007% increase in food security. Other variables, such as rainfall, capital expenditure, and consumption expenditure, positively influenced food security, whereas rural and urban population growth negatively impacted it. Conclusions: Agricultural exports play a critical role in enhancing food security in Zimbabwe by generating foreign currency and promoting investment in the agricultural sector. However, demographic pressures and climate-related risks remain significant challenges. Limitations: The study is limited by data availability, as annual data may overlook short-term changes. Additionally, some potentially influential variables were excluded because of data constraints. Contribution: This study contributes empirical evidence to policy debates on balancing export-oriented agriculture with domestic food needs. It offers actionable insights for government ministries and institutions involved in agricultural planning, advocating greater support for capital investment, infrastructure, and farmer education to ensure sustainable food security outcomes.